Assessing Computer Literacy and Socioreligious Perspectives among First-Year Cadets in International Maritime Education at Maritime Institute Jakarta (STIP Jakarta) - Panderaja Soritua Sijabat; Marudut Bernadtua Simanjuntak (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This academic research delves into the critical examination of the computer literacy and socioreligious perspectives of first-year cadets enrolled in the International Maritime Education programme at Maritime Institute Jakarta (STIP Jakarta). The study focuses on 200 randomly selected cadets who represent a diverse range of cultural and linguistic backgrounds within Indonesia. As future global officers, these cadets are integral to the maritime sector's international landscape and are expected to communicate fluently in English, adhering to the standards set by the International Maritime Organization's International Maritime Education and Training (IMO-STCW) guidelines. The research is centred on the first semester cadets, freshly graduated from senior high school, enrolled in three majors: Nautical, Technical, and Port and Shipping Management. These majors collectively contribute to the production of qualified seamen, deck officers, and engine officers. The investigation employs qualitative research methods and descriptive analysis to comprehend the cadets' competences in computer literacy. The focal point is the introductory study of computer science and maritime technology tailored for the Nautical and Technical majors. Moreover, the research incorporates an examination of the socioreligious dimensions influencing the cadets' perspectives on their educational journey. Given that the cadets hail from diverse regions of Indonesia, they bring with them a rich tapestry of linguistic and cultural practices, utilising both Bahasa Indonesia and their traditional languages in their daily lives. The study aims to understand how these socioreligious factors intertwine with their academic pursuits and adherence to international standards. In conclusion, this research contributes to the broader discourse on maritime education by providing insights into the intersection of computer literacy, socioreligious perspectives, and international competencies among first-year cadets. The findings are expected to inform educational strategies and policies to better prepare cadets for the evolving demands of the global maritime industry.